SOMATOTYPE AND PHYSICAL DEVELOPMENT OF 11-YEAR-OLD GIRLS DURING HANDBALL TRAINING - H. Draganova (Trakia Journal of Sciences)
Nowadays, knowledge of body structure is increasingly attracting the interest of the scientific community, as it is known to be relevant to performance in sports.The present study is aimed at tracking the dynamics of anthropometric indicators and somatotype in 11-year-old girls. During their training in the subject "Physical Education and Sports" at school, a specialized handball training program was implemented. The research contingent is 100 girls aged 11 years. The subjects were tested at the beginning and at the end of the experiment, which was conducted during the academic year 2021/2022. The data were processed mathematically and statistically, applying variation analysis.